Purification and biochemical characterization of a mycelial alkaline phosphatase without DNAase activity produced byAspergillus caespitosus - Guimarães, L. H. S.; Júnior, A. B.; Jorge, J. A.; Terenzi, H. F.; Polizeli, M. L. T. M. (Folia microbiologica, 2007)
Biochemical properties of a termostable alkaline phosphatase obtained from the mycelium extract ofA. caespitosus were described. The enzyme was purified 42-fold with 32 % recovery by DEAE-cellulose and concanavalin A-Sepharose chromatography. The molar mass estimated by Sephacryl S-200 or by 7 % SDS-PAGE was 138 kDa and 71 kDa, respectively, indicating a homodimer. Temperature and pH optima were 80 °C and pH 9.0. This enzyme was highly glycosylated (≈74 % saccharide content). The activity was enhanced by Mg2+ (19–139 %), NH4+ (64 %), Na+ (51 %) and Mn2+ (38 %). 4-Nitrophenyl phosphate (4-NPP) was preferentially hydrolyzed, but glucose 1-phosphate (93 %), UTP (67 %) andO-phosphoamino acids also acted as substrates.νlim andKm were 3.78 nkat per mg protein and 270 µmol/L in the absence of Mg2+ and 7.35 nkat per mg protein and 410 µmol/L in the presence of Mg2+, using 4-NPP as substrate. The purified alkaline phosphatase removed the 5′-phosphate group of a linearized plasmid without showing DNAase activity, indicating its potential for recombinant DNA technology.